1999
DOI: 10.1680/macr.1999.51.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Size-effect tests in unreinforced concrete columns

Abstract: Test results obtained as part of a size-effect study on axially loaded plain concrete columns are presented. The test specimens were geometrically similar concrete columns (with dimensions in the ratio 1:2:4) having slenderness ratios of 9·7, 18·0 and 34·7. The columns were of square cross-section with sides of 50, 100 and 200 mm and varied in length from 145 mm to 2080 mm. Although such columns are at the bottom end of practical column sizes, the test results extend existing research information on size effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…Previous related research (Sener et al, 1999(Sener et al, , 2004Wang and Wu, 2011) shows that both the peak strength and the post-peak behaviour of concrete columns may exhibit scale effects, which are more obvious when HSC is used in the columns. The scale effect of SRHC columns may be complicated owing to the high strength of concrete and the interaction between concrete and steel (longitudinal bars, structural steel, stirrups), and is beyond the scope of this paper.…”
Section: Specimens and Test Variablesmentioning
confidence: 99%
“…Previous related research (Sener et al, 1999(Sener et al, , 2004Wang and Wu, 2011) shows that both the peak strength and the post-peak behaviour of concrete columns may exhibit scale effects, which are more obvious when HSC is used in the columns. The scale effect of SRHC columns may be complicated owing to the high strength of concrete and the interaction between concrete and steel (longitudinal bars, structural steel, stirrups), and is beyond the scope of this paper.…”
Section: Specimens and Test Variablesmentioning
confidence: 99%
“…So far, lots of efforts have been conducted to explore the failure behavior and size effect of RC columns, for example, in the experimental efforts 4,6,7 and the numerical efforts. 8,[12][13][14][15] However, the size range of the tested concrete components was still limited to a relatively small range, and most of these efforts were focused on the RC columns having square cross section.…”
Section: Size Effect In Rc Columnsmentioning
confidence: 99%
“…It is increasingly being accepted that size effect exists in concretes. [1][2][3] In addition, numerous experimental observations [4][5][6][7][8][9][10] have indicated that size effect also existed in RC members involving beams, columns, and beam-column connections. As the dimensions of engineering structures are becoming larger and larger, the safety of these largesized constructions has become one of the most concerned topics.…”
Section: Introductionmentioning
confidence: 99%
“…长细比对钢筋混凝土柱的受力力学性能有着显 著的影响, 长细比较大时, 容易发生失稳破坏, 通常 表现为屈曲失效, 其名义轴压强度在一定长细比范 围内较为稳定, 超出某临界值后则随长细比增加而 逐渐减小, 表现为屈曲强度的降低 [3] . 针对钢筋混凝 土柱长细比效应问题, Bažant 等人 [4] 、于峰和牛荻 涛 [5] 、Lim 和 Ozbakkaloglu [6] 、邹捷等人 [7] 从理论上对 钢筋混凝土柱的长细比效应进行了探讨; Bažant 和 Kwon [8] 、Şener 等人 [9,10] 、Němeček 和 Bittnar [11] 、陈 宝春和欧智菁 [12] 、张光玮等人 [13] 、张磊等人 [14] 则对 钢筋混凝土柱的长细比效应进行了试验研究. 这些 研究工作均证实了长细比效应对钢筋混凝土柱最终 破坏模式及其名义轴压强度存在显著影响.…”
Section: 引言unclassified